PROSES INTEGRASI SIKAP SOSIAL DAN SPIRITUAL DALAM PEMBELAJARAN MATEMATIKA PADA SISWA KELAS VII SMP NEGERI DI KECAMATAN PURWODADI - Asmarawati, Endah; Riyadi, Riyadi; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purposes of this study were to describe: (1) how the teachers prepared learning activities to integrate social and spiritual attitude, (2) the integration of social and spiritual attitude in teaching and learning, (3) how teachers assessed the social and spiritual attitudes. Qualitative research was applied in this research.The subjects of the research were seventh grade mathematics teachers in Purwodadi Subdistrict and the subjects selection criteria were based on teachers who had followed the training curriculum in 2013 and recommended by the headmaster of the schools. The subjects are selected based on specific criteria by usingÂ  snowball sampling technique. Source of data derived from informants (teachers and students), documentation and learning process. The data collection technique was done by observation, interviews and documentation. Data analysis used Miles and Hubermanâs concept that are data collection, data reduction, presenting the data, and drawing the conclusion. The validity of the data used source triangulation. The results of the study could be concluded as follows. (1) Preparation of learning activities to integrade spiritual attitude made by reviewing KI 1, choose the appropriate KD, making the indicator, developing the material, made the instrument to measure the spiritual attitude. While the preparation of learning activities that integrate social attitudes conducted by reviewing KI 2, choose the appropriate KD, making the indicator, developing the material, made the instrument to measure social attitudes. (2) Integration process of spiritual attitudes was conducted by the teachers in preliminary activities and in the core activities by providing motivation or encouragement, direction, and warning to students through a set of examples of Gods creation that is in their everyday lives. Spiritual attitudes developed by teachers were grateful and fear of God Almighty. Integration process of social attitudes conducted by teachers in preliminary activities, core activities and close activities with the teacher giving cover modelling, assignment, and referrals through examples of phenomena that exist in everyday life associated with the material set. Social attitudes developed by teachers were discipline, mutual help, caring, responsibility and tolerance. (3) The teachers made assessment of spiritual attitude in three ways: observation, journals and self-assessment. The teachers made assessment of social attitudes in three ways: observation, journals and peer assessment.Keywords: attitudes integration process, social attitudes, spiritual attitude, attitude assessment process.